A CRITICAL REVIEW OF THE USEFULNESS OF SEGMENTAL REPORTING BY MAJOR INTERNATIONAL BANKS - Pratt, David (2005)
This study critically reviews the usefulness of segment reporting by two multinational banks using a residual earning valuation model to assess whether valuation of the individual segments of each bank is possible. The two banks selected for the study were the Royal Bank of Canada and HSBC Group Plc. Qualitative analysis of the annual reports from 1997 to 2004 for the Royal Bank of Canada and the current 2004 annual report for HSBC were used as the basis for determination.